Bleaching Bamboo Fibre Using Eco Enzyme from Food Waste - Azman, Muhammad Zuhairi; Che Pa, Ts. Dr. Nasrul Fikry (Progress in Engineering Application and Technology, 2022)
The use of synthetic fibres has caused various environmental problems because carbon and glass fibres are not readily biodegradable and act as pollutant to the environment. Natural plant such as bamboo was introduced to replace synthetic fibres hence the need for bleaching. This research is aimed to study the effect of natural bleaching agent known as eco enzyme on bamboo fibres and compare the results with conventional bleaching agent. The most suitable condition for eco enzyme was analysed and discussed thoroughly. Bamboo fibres were bleached with eco enzyme in different temperature (35°C, 50°C, 70°C) and bleached time (60, 90, 120 minutes) accordingly and further oven dried at 40℃ - 48℃. Tensile strength and whiteness of the resulting bleached fibres are analysed. Both parameter on the bleach fibre significantly improved compared to untreated fibre with tensile strength increase 64.59% at temperature of 35°C - 50°C and 60 - 90 minutes bleaching, whereas for whiteness it increases 21.7% at temperature of 50°C and 60 minutes bleaching. In conclusion, eco enzyme provides better result compared to hydrogen peroxide in term of bleaching duration at considerably low temperature.